Axiomatization of a Basic Logic of Logical Bilattices - Takano, Mitio (Bulletin of the Section of Logic, 2016)
A sequential axiomatization is given for the 16-valued logic that has been proposed by Shramko-Wansing (J Philos Logic 34:121–153, 2005) as a candidate for the basic logic of logical bilattices.